2021
DOI: 10.52700/jn.v2i2.44
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Yttrium doping on the physical properties of ErMn2O5

Abstract: We have investigated the structural and electrical properties of perovskite system Er1-xYxMn2O5 (x=0, 0.2, 0.4, 0.6, 0.8 and 1.0) synthesized by sol gel method. The structural behavior is probed by the single phase formation of the compositions and orthorhombic symmetry confirmed by X-ray diffraction Rietvield analysis. The electrical behavior of the system is explained in terms of dc temperature dependent electrical resisitivity and Mott variable range hoping (VRH) which supports the semicondicting behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…However, as concentration increases, the band gap increases slightly from 1.36--1.39 eV for the direct band gap and 1.4-1.44 eV for the indirect band gap respectively. Similar studies were undertaken for GdMn 2 O 5 and YMn 2 O 5 , by Ahmad et al 12 and reported that the band gap values are 1.8 eV and 1.4 eV respectively. The change in the band gap value of GdMn 2 O 5 may be due to the preparation method.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…However, as concentration increases, the band gap increases slightly from 1.36--1.39 eV for the direct band gap and 1.4-1.44 eV for the indirect band gap respectively. Similar studies were undertaken for GdMn 2 O 5 and YMn 2 O 5 , by Ahmad et al 12 and reported that the band gap values are 1.8 eV and 1.4 eV respectively. The change in the band gap value of GdMn 2 O 5 may be due to the preparation method.…”
Section: Resultssupporting
confidence: 71%
“…Khannanov et al 11 studied the electric polarization induced by phase separation in multiferroic GdMn 2 O 5 at room temperature, and reported that the magnetic field is influencing the polarisation, indicating the existence of magnetoelectric interaction. Javed Ahmad et al 12 studied the electrical and dielectric properties of Y doped GdMn 2 O 5 and observed the hardening behaviour of phonons as the doping concentration increases, and attributed this to the difference in molar mass and thus decrease in cell volume. They also reported that the rare Earth movement is responsible for low frequency phonons shifts whereas O-ions contribute at higher frequency modes and these observations indicate the stretching motion of MnO 6 octahedra caused by changes in cell volume.…”
mentioning
confidence: 99%